Analisis Kesulitan Belajar dalam Menulis Tegak Bersambung pada Siswa Kelas 2 SDN Banyuajuh 2 Kamal - Ahmad Rizal (Jurnal Pengembangan dan Evaluasi Pendidikan, 2024)
This study aims to analyze learning difficulties in writing cursively in grade 2 students. The type of research used is qualitative research using a descriptive approach. The data collection techniques used in this research were interviews and observation. Based on the results of the analysis from interviews and observations carried out, researchers found difficulties faced by students, especially in writing cursively. The difficulties experienced by students include not being able to arrange or combine cursive letters, when writing they do not match the lines provided in the soft book, and when writing at the beginning of sentences they do not use capital letters. To overcome this, teachers carry out habituation by providing cursive writing practice during lessons or giving assignments as homework so that students can get used to it so that their cursive writing skills can be improved.